Demodulation and purification of ellagic acid from pomegranate fruit and study antimicrobial activity against the pathogenic bacteria - Hiba H. R; Eesa. M. Thalij; Sundus J. M. (Tikrit Journal of Pure Science)
The ellagic acid is isolated from  pomegranate fruit by liquid–liquid extraction method. This method includes extraction  with 20% (v/v) methanol under reflux conditions for  purification of acid by preparative TLC method using glass plates (20 × 20 cm) coated with silica gel .This acid was detected by TLC, HPLC, UV methods and functional group of the acidwhich was extracted by FTIR technique. The antibacterial activity of Ellagic acid extract of pomegranate fruit  powder was defined by petri Dish technique versus different microbial types, Gram-positive (Staphylococcus aureus), Gram-negative (Escherichia coli, Pseudomonas aeruginosa) and two Yeasts(C. glabrata and C. albicams).